Graphene/Organic Semiconductor Heterojunction Phototransistors with Broadband and Bi‐directional Photoresponse. Issue 49 (1st October 2018) - Han, Jiayue; Wang, Jun; Yang, Ming; Kong, Xiao; Chen, Xiaoqing; Huang, Zehua; Guo, Hui; Gou, Jun; Tao, Silu; Liu, Zhijun; Wu, Zhiming; Jiang, Yadong; et al.
Abstract: A graphene–semiconductor heterojunction is very attractive for realizing highly sensitive phototransistors due to the strong absorption of the semiconductor layer and the fast charge transport in the graphene. However, the photoresponse is usually limited to a narrow spectral range determined by the bandgap of the semiconductor. Here, an organic heterojunction (C60 /pentacene) is incorporated on graphene to realize a broadband (405–1550 nm) phototransistor with a high gain of 5.2 × 10 5 and a response time down to 275 µs. The visible and near‐infrared parts of the photoresponsivity (9127 A W −1 @650 nm and 1800 A W −1 @808 nm) come from the absorption of the organic layer and the graphene, respectively. For the first time, a bi‐directional (positive and negative) photoresponse is demonstrated at different wavelengths, due to the opposite charge transfer direction of the photoexcited carriers enforced by the unique band alignment. Such tunability will enable new functionalities such as large‐scale real‐time optical image and infrared focal plane array detection in the future. Abstract : An organic heterojunction (C60 /pentacene) on graphene is incorporated to realize a broadband (405–1550 nm) phototransistor with high gain of 5.2 × 10 5 and response time down to 275 µs. For the first time, a bi‐directional (positive and negative) photoresponse is demonstrated at different wavelengths, due to the opposite charge transfer direction of the photoexcited carriers enforced by the unique band alignment.